Guideline for management of septic arthritis in native joints (SANJO) - Ravn, Christen; Neyt, Jeroen; Benito, Natividad; Abreu, Miguel Araújo; Achermann, Yvonne; Bozhkova, Svetlana; Coorevits, Liselotte; Ferrari, Matteo Carlo; Gammelsrud, Karianne Wiger; Gerlach, Ulf-Joachim; Giannitsioti, Efthymia; Gottliebsen, Martin; et al. (Journal of bone and joint infection, 2023)
This clinical guideline is intended for use by orthopedic surgeons and physicians who care for patients with possible or documented septic arthritis of a native joint (SANJO). It includes evidence and opinion-based recommendations for the diagnosis and management of patients with SANJO.